2012
DOI: 10.15560/8.5.940
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the brachyuran crabs (Crustacea: Decapoda) in the rocky subtidal of Vitória Archipelago, southeast coast of Brazil

Abstract: Biodiversity can be useful as an ecosystem indicator for conservation and monitoring, through continuous assessment of its main properties including stability, primary productivity, exploitation tolerance and even global environmental changes. The main purpose of this study was to provide a checklist of the crabs associated with subtidal rocky bottoms at the Vitoria Archipelago, southeastern Brazilian coast. Monthly collections were carried out from February 2004 through January 2006 on three islands at the Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…The absence of records of these species until the present is likely due to their cryptic habit, as well as to low collection efforts in the rocky subtidal of this region (e.g., Mantelatto et al, 2004aMantelatto et al, , 2004bCobo, 2006;Alves et al, 2011;Alves et al, 2012). However, the possibility remains that these shrimps crossed this biological filter through accidental transport, such as in ballast water, as previously recorded for other species of decapod crustaceans (e.g., Mantelatto & Dias 1999;Alves et al, 2006;Tavares, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…The absence of records of these species until the present is likely due to their cryptic habit, as well as to low collection efforts in the rocky subtidal of this region (e.g., Mantelatto et al, 2004aMantelatto et al, , 2004bCobo, 2006;Alves et al, 2011;Alves et al, 2012). However, the possibility remains that these shrimps crossed this biological filter through accidental transport, such as in ballast water, as previously recorded for other species of decapod crustaceans (e.g., Mantelatto & Dias 1999;Alves et al, 2006;Tavares, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, a deviation from 1:1 in favor of the females was recorded for H. paulensis. Alves et al (2012) also observed the occurrence of an elevated number of females compared to males of the same species, but in a consolidated substrate. Such deviations might indicate a common pattern for H. paulensis in the study region.…”
Section: Population Structurementioning
confidence: 77%
“…The occurrence of individuals in the stations nearer to the continent and exposed to wave action (7.5 and 10 m) was remarkable in this study. This is probably due to their proximity to the rocky shores, where H. paulensis is frequently found (Alves et al, 2012) as this kind of habitat receives deposits of allochthonous material from the continent and small rivers.…”
Section: Spatio-temporal Variations Of the Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, an increasing number of studies in Brazil with decapods were made using scuba diving (Bouzon & Freire, 2007;Alves et al, 2012;Giraldes et al, 2015;Soledade et al, 2015).…”
Section: __________________ Corresponding Editor: Ingo Wehrtmannmentioning
confidence: 99%